2013
DOI: 10.3109/08820139.2013.782317
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Regulates T Cell Proliferation in a Tissue and Subset-Specific Manner During Normal Mouse Pregnancy

Abstract: The regulation of T cell homeostasis during pregnancy has important implications for maternal tolerance and immunity. Evidence suggests that Programmed Death-1 (PD-1) participates in regulation of T cell homeostasis and peripheral tolerance. To examine the contribution of PD-1 signaling on T cell homeostasis during normal mouse pregnancy, we examined T cell number or proportion, PD-1 expression, proliferation, and apoptosis by flow cytometry, BrdU incorporation, and TUNEL assay in pregnant mice given anti-PD-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 85 publications
(108 reference statements)
2
19
0
Order By: Relevance
“…Most research concerning inflammation‐induced preterm labor has therefore focused on the innate limb of immunity . Yet, several studies reported strong evidence that T cells, the primary cellular component of the adaptive immune system, are present at the maternal‐fetal interface . More recently, we provided evidence indicating that T cells are also implicated in the mechanisms that lead to labor at term and spontaneous preterm labor .…”
Section: Introductionmentioning
confidence: 81%
“…Most research concerning inflammation‐induced preterm labor has therefore focused on the innate limb of immunity . Yet, several studies reported strong evidence that T cells, the primary cellular component of the adaptive immune system, are present at the maternal‐fetal interface . More recently, we provided evidence indicating that T cells are also implicated in the mechanisms that lead to labor at term and spontaneous preterm labor .…”
Section: Introductionmentioning
confidence: 81%
“…A number of other factors also appear to affect the trafficking of effector T-cells through the decidua, including cytokines (such as TGFβ, IL-10, CCL2), hormones (progesterone, corticotropin-releasing hormone, PGs), Fas-Fas ligand signaling, HLA-G, Programmed Death-1 (PD-1), and other molecules that affect T-cell metabolism (such as tryptophan) (Bonney and Matzinger 1998; Kalantaridou et al 2007; Xiong et al 2010; Silasi and Mor 2012; Shepard and Bonney 2013; Nancy and Erlebacher 2014; Wu et al 2014). Tryptophan is an essential amino required for T-cell activation.…”
Section: Why Does the Human Uterus Only Support A Pregnancy For Nine mentioning
confidence: 99%
“…[21][22][23][24] We have studied T-cell homeostasis in mice and observed changes in the maternal immune system that persist PP. [21][22][23][25][26][27] There may be accumulation of TREGs in PP that may protect subsequent pregnancies. 28,29 Abnormal pregnancy, including preeclampsia [30][31][32][33][34][35] and preterm birth, 36 is associated with immune system dysregulation.…”
Section: Introductionmentioning
confidence: 99%